Elution of divalent cations from iron ore mining waste in an indirect aqueous mineral carbonation for carbon capture and storage - Soomro, Muhammad Hameer; Mohd Kusin, Faradiella; Mohamat-Yusuff, Ferdaus; Nik Daud, Nik Norsyahariati (MDPI AG, 2024)
Mining waste is generated in vast quantities globally, which can have negative environmental consequences. This study highlights the utilization of iron ore mining waste as feedstock material in the preparatory step of an indirect aqueous mineral carbonation for carbon sequestration. The role of reactive cations (Ca2+, Mg2+, and Fe2+) was investigated in view of their elution behavior to improve carbonation efficiency. An elution experiment was carried out for the divalent cations using different acids (oxalic, HCl, acetic, and formic acid) at different concentration solutions (up to 1.5 M) and times (up to 100 min) at ambient temperature. The initial analysis confirmed the presence of divalent cations in the sample. The elution approach at ambient temperature resulted in the elution efficiency of Fe2+ (30.4%), Mg2+ (54%) using oxalic acid, and Ca2+ (98%) using HCl at a relatively short time between 50 and 100 min. It was found that for the iron ore mining waste, oxalic acid and HCl were best suited as elution agents for the Fe2+ and Mg2+, and Ca2+, respectively. The CO2 sequestration potential was calculated to be 131.58 g CO2/kg residue. A further carbonation step using a complexing agent (1,10 phenanthroline) confirmed the formation of siderite and magnesite along with phenanthroline hydrates. Findings have shown that the indirect mineral carbonation of the iron mining waste with complexing agent might improve carbonation efficiency, thus indicating that this material is useful for long-term carbon capture and storage applications.